Reliability and optimization of structural systems : assessment, design and life-cycle performance : proceedings of the thirteenth IFIP WG 7.5 Working Conference on Reliability and Optimization of Structural Systems, Kobe, Japan, October 11-14, 2006 /: assessment, design and life-cycle performance : proceedings of the thirteenth IFIP WG 7.5 Working Conference on Reliability and Optimization of Structural Systems, Kobe, Japan, October 11-14, 2006. ([2007]) - Unknown
No abstract available